Searching Optimum Route With Variable Travel Time - Yamauchi Shuki; Tokunaga Junpei; Ebara Hiroyuki; Ueda Naonori (IEEE Access)
In the near future, in a society where connected and autonomous vehicles (connected automated vehicles) enable the transmission and sharing of traffic information, the demand for navigation systems is expected to increase; based on this background, this study proposes a shortest route search method using a time-expansion network. Assuming that the travel time to the destination can be accurately predicted, the proposed Method 1 finds a route that can reach the destination in the shortest possible travel time. This results in more realistic and accurate travel times than those provided by the current method. The proposed Method 2 facilitates vehicle dispersion by allowing drivers to set arrival times at their destinations in advance. We believe that this will alleviate the total level of congestion on the road by distributing routes according to the arrival time established by the drivers.We are convinced that if more vehicles were to use our proposed methods, energy consumption would be reduced in society as a whole.